UNA MALA COMPRENSIÓN DE WITTGENSTEIN - Valdés Villanueva, Luis M. (Daimon Revista Internacional de Filosofia, 1990)
The aim of this paper is to show that Saul Kripke´s interpretation of Wittgenstein´s private languaje argument is misleading when he presents him as a sceptical. However it is argued that, in spite of this misunderstanding, Kripke reaches what possibly would be a correct answer to the rule-following problem: the community view.